LABA EKONOMIS VERSUS LABA AKUNTANSI DALAM MEMPREDIKSI KENAIKAN ATAU PENURUNAN HARGA SAHAM PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2012-2013 - Pangaribuan, Jonner (UNIKA Santo Thomas, 2013)
So many researches had been conducted to find out what factors infuenced the stock prices. So far there is no same conclusion regarding this. Based on theoritical approach the price is affeceted by achieved profit which is reported in finacial statements. Not satisfied by this approach researchers develope a more comprehensive approach which is known as EVA.In this concept cost of capital is considered ,analysis is not merely based on profit any more.Procit based on acounting approach versus profit based on economical approach. Do EVA can explain the prica change? Wich profit can explain more clearly? The resut of analysis shows that EVA(Economical Profit) can explain more clearly than Accounting Profit